2020
DOI: 10.3390/genes12010001
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing Identifies Novel De Novo Variants Interacting with Six Gene Networks in Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a highly heritable condition caused by a combination of environmental and genetic factors such as de novo and inherited variants, as well as rare or common variants among hundreds of related genes. Previous genome-wide association studies have identified susceptibility genes; however, most ASD-associated genes remain undiscovered. This study aimed to examine rare de novo variants to identify genetic risk factors of ASD using whole exome sequencing (WES), functional characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Missense variants in one gene, CEP41 , associated significantly with ASD [ 65 ] and overexpression of CEP41 pathogenic alleles in zebrafish model, showed that variants in embryos induces axonal defects and also affects cranial neural crest (CNC) cell migration and exhibited deficits in social behavior. More recently, Kim and co-workers [ 66 ] performed WES on 51 Korean families (n = 151 individuals) to identify putative causal variants of ASD and identified 36 de novo variants, which were confirmed by Sanger sequencing (27 missense, two silent, one nonsense, one splice region, one splice site, one 5′ UTR, one intronic SNVs, and two frameshift deletions). A retrospective study on 343 ASD patients using different genetic approaches of FMR1 testing, chromosomal microarray (CMA) and/or WES, recommend WES as the first-tier approach in the diagnosis of ASD patients [ 67 ].…”
Section: Genetics Studiesmentioning
confidence: 99%
“…Missense variants in one gene, CEP41 , associated significantly with ASD [ 65 ] and overexpression of CEP41 pathogenic alleles in zebrafish model, showed that variants in embryos induces axonal defects and also affects cranial neural crest (CNC) cell migration and exhibited deficits in social behavior. More recently, Kim and co-workers [ 66 ] performed WES on 51 Korean families (n = 151 individuals) to identify putative causal variants of ASD and identified 36 de novo variants, which were confirmed by Sanger sequencing (27 missense, two silent, one nonsense, one splice region, one splice site, one 5′ UTR, one intronic SNVs, and two frameshift deletions). A retrospective study on 343 ASD patients using different genetic approaches of FMR1 testing, chromosomal microarray (CMA) and/or WES, recommend WES as the first-tier approach in the diagnosis of ASD patients [ 67 ].…”
Section: Genetics Studiesmentioning
confidence: 99%
“…More importantly, as well as these preclinical problems others such as possible off-target problems or immunogenicity linked with the use of Cas9 39 may delay their clinical application. However, while gene editing as therapeutic option still needs further development, CRISPR/Cas9 methodology has been applied to provide a large number of new animal models to further understand DMD pathology and perform preclinical studies 40 .…”
Section: Introductionmentioning
confidence: 99%
“…Adenylate Cyclases 7 and 9 ( ADCY7 and ADCY9 ) are membrane-bound enzymes that catalyze the formation of cyclic AMP from ATP and are highly expressed in the brain. De novo mutations in ADCY7 have been reported in autism spectrum disorders (ASD) where the gene has been proposed to be a risk factor [ 39 ]. ASD and RTT share some commonalities with RTT individuals showing some ASD-like behaviors [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%